1992
DOI: 10.1095/biolreprod47.6.977
|View full text |Cite
|
Sign up to set email alerts
|

Source of Immunoreactive Inhibin in the Chicken Ovary1

Abstract: High concentrations of immunoreactive inhibin were detected in the plasma of the laying domestic hen using a heterologous RIA validated for use in the chicken. Cessation of egg production induced by restricting the intake of nutrients decreased circulating inhibin to approximately 20% of its original concentration within 8 days, indicating that the ovary is the major source of the measured material. Dissection of ovarian follicles revealed that inhibin is nearly exclusively produced in the granulosa cell layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…In the present study, the inhibin α and inhibin/activin βA and βB subunits were expressed in the granulosa cells of all follicles during different stages of development from 1 to 7 weeks after hatching, indicating that granulosa cells may secrete dimeric and bioactive inhibins during the follicular development of Japanese quails. Immunolocalization of the inhibin/activin subunits in the granulosa cells of the quail ovary is in agreement with previous studies showing that the granulosa cells of chicken [18,19] and duck [30,31] ovaries are the major source of inhibin. In hens, the greatest amount of mRNA expression for the inhibin/activin βA subunit is found in the F1 follicle, while the inhibin α subunit is expressed more abundantly than the inhibin βA subunit in large preovulatory follicles.…”
Section: Sedqyar Et Al 56supporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the inhibin α and inhibin/activin βA and βB subunits were expressed in the granulosa cells of all follicles during different stages of development from 1 to 7 weeks after hatching, indicating that granulosa cells may secrete dimeric and bioactive inhibins during the follicular development of Japanese quails. Immunolocalization of the inhibin/activin subunits in the granulosa cells of the quail ovary is in agreement with previous studies showing that the granulosa cells of chicken [18,19] and duck [30,31] ovaries are the major source of inhibin. In hens, the greatest amount of mRNA expression for the inhibin/activin βA subunit is found in the F1 follicle, while the inhibin α subunit is expressed more abundantly than the inhibin βA subunit in large preovulatory follicles.…”
Section: Sedqyar Et Al 56supporting
confidence: 92%
“…Inhibins selectively suppress [7][8][9][10][11][12] while activins stimulate [11][12][13][14][15] the release of FSH. Previous studies have shown that the avian ovary also produces inhibins, which plays important roles in the regulation of pituitary FSH [16][17][18][19][20][21]. However, the roles of inhibins have received little attention in quail.…”
mentioning
confidence: 99%
“…In addition, inhibins and activins have been shown to exert paracrine/autocrine effects on steroidogenesis and folliculogenesis in the ovary (Findlay, 1993). Chick inhibin is likely to play important roles in the regulation of pituitary FSH secretion (Akashiba et al, 1988;Tsonis et al, 1988;Vanmontfort et al, 1992;Johnson et al, 1993a, b) as well as mammalian inhibin. In the hen, the ovarian follicles have been demonstrated to be a major source of circulating immunoreactive (ir-) inhibin Johnson et al, 1993a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Vanmontfort et al (1992) cultured granulosa cells from hen preovulatory (F1-F4) follicles and found that secretion of immunoreactive inhibin was highest from F4 follicles and lowest in F1 follicles. Secretion of immunoreactive inhibin was stimulated by both LH and FSH.…”
mentioning
confidence: 99%
“…Secretion of immunoreactive inhibin was stimulated by both LH and FSH. However, the inhibin radioimmunoassay used in the study of Vanmontfort et al (1992) has limited specificity and crossreacts extensively (100%) with free inhibin α-subunit forms. The high concentrations of inhibin α-subunit present in hen plasma (Lovell et al, 2000a(Lovell et al, , 2001, cockerel plasma (Lovell et al, 2000b) and F1 preovulatory follicle granulosa cell extract (Lovell et al, 1998) signal the need for caution in interpreting earlier findings based on the use of 'first generation' inhibin radioimmunoassays lacking specificity for the αβ dimeric molecule.…”
mentioning
confidence: 99%